Minority representation and the quest for voting equality / Bernard Grofman, Lisa Handley, Richard G. Niemi. - Grofman, Bernard; Handley, Lisa; Niemi, Richard G. (Cambridge University Press, 1992)
This book provides an up-to-date analysis of American voting rights law and the numerous controversies surrounding minority representation. Written by authors with first-hand experience in the case law, the book details the evolution of the law and precedent from 1965 onwards. The authors explain the logic underlying the major decisions, introduce the reader to the procedures for establishing standards of representation and measuring discrimination, and discuss the major points of recent contention. In conclusion, they address the implications of recent developments in voting rights law for the future of representation in America.